Analisis Penerapan Presensi Berbasis Aplikasi Mobile Pada Pegawai Perpustakaan Nasional RI - Firda Amelia; Susan Febriantina; Bayu Suhendry (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
This study aims to analyze the implementation of mobile application-based attendance for employees at the National Library of the Republic Of Indonesia through the Staffinc Work application, identify the challenges encountered, adn evaluate the system’s implementation. This study employed a qualitative approach with a descriptive method. Data were collected through interview, observation, and documentation involving five informants who are directly engaged in the use and management of the mobile application based attendance system. Data analysis was conducted systematically using Nvivo 15 software. The findings reveal that the mobile application-based attendance system has had a positive impact on employee attendance recording, reduced queuing during clock-in and clock-out times, and provided flexibility through the use of personal devices. Nevertheless, the system still faces challenges including internet disruptions, system errors during application updates, vendor dependency, and the lack of direct integration with the SDMU Bureau's HR portal, resulting in attendance data still being managed semi-digitally. System evaluation is conducted periodically through vendor-driven improvements and feature development to support integrated HR services within a single platform. This study is expected to serve as a reference for developing a more effective and sustainable digital attendance system.